2004
DOI: 10.1055/s-2004-820882
|View full text |Cite
|
Sign up to set email alerts
|

Water Sources and Water‐Use Efficiency in Mediterranean Coastal Dune Vegetation

Abstract: In coastal environments plants have to cope with various water sources: rainwater, water table, seawater, and mixtures. These are usually characterized by different isotopic signatures ( (18)O/ (16)O and D/H ratios). Xylem water reflects the isotopic compositions of the water sources. Additionally, water-use efficiency (WUE) can be assessed with carbon isotope discrimination (Delta) analyses. Gas exchange, Delta of leaf dry matter, and isotopic composition (delta (18)O) of xylem water were measured from June t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 28 publications
(32 reference statements)
3
43
0
1
Order By: Relevance
“…A detailed study on water use under drought stress for the most representative species of the dune vegetation is proposed by Mereu et al, 2009. A strong physiological dependence of schlerophyllous plants on the freshwater table level was also observed, in our same experimental site, with a study of isotopic fractionation in xylematic water (Alessio et al, 2004). In particular, the shrubs examined in our study, and particularly A. unedo, P. latifolia and, Q. ilex, showed negative values of 18 O 2 values of xylematic water that are associated with high discrimination ( ) values, even under very dry conditions.…”
Section: Vegetation Characteristicsmentioning
confidence: 54%
See 2 more Smart Citations
“…A detailed study on water use under drought stress for the most representative species of the dune vegetation is proposed by Mereu et al, 2009. A strong physiological dependence of schlerophyllous plants on the freshwater table level was also observed, in our same experimental site, with a study of isotopic fractionation in xylematic water (Alessio et al, 2004). In particular, the shrubs examined in our study, and particularly A. unedo, P. latifolia and, Q. ilex, showed negative values of 18 O 2 values of xylematic water that are associated with high discrimination ( ) values, even under very dry conditions.…”
Section: Vegetation Characteristicsmentioning
confidence: 54%
“…The weak emission of monoterpenes by Arbutus unedo (0.29 µg(C) g −1 DW h −1 ), was also observed by Owen et al (1997), and Pio et al (1993). Alessio et al (2004) also reported inconspicuous emissions of isoprenoids by Arbutus unedo and Phillyrea latifolia. It is therefore confirmed that these plants do not have the capacity to produce and emit relevant amounts of isoprenoids.…”
Section: Isoprenoid Emissionmentioning
confidence: 92%
See 1 more Smart Citation
“…Water status depends on water availability, and on the extension of plant root systems to reach water available in deeper soil layers when shallow reserves dry out during the summer season. Those species that keep their levels of foliar hydration and suffer less water stress (Alessio et al 2004) are certainly less prone to fire.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen isotope value of surface soil water corresponding to plants root system depth at different sampling points of two sections shown as Table 3. Only at sampling point 3 of section I the oxygen isotope value of soil water was similar with corresponding oxygen isotope value of plants leaf water, at others sampling points the oxygen isotope values of soil water were less than corresponding oxygen isotope values of plants leaf water, the reasons shown as: (1) the isotope fractionation was not occurred when water absorbed by plants root system and conveyed to leaves [25,26] , but when the leaf water directly contacted with the air, heavy isotope in leaf water will enriched with plant transpiration [27] . (2) …”
Section: δ 18 O Values Of Plants Leaf Watermentioning
confidence: 99%